TWO-PROBE EXCITED CIRCULAR RING ANTENNA FOR MIMO APPLICATION - Monai Krairiksh; Panisa Keowsawat; Chuwong Phongcharoenpanich; Sompol Kosulvit (My University, 2009)
This paper presents the analysis and design of a two-probe excited circular ring antenna.The analysis is conducted by using induced emf method and transmission line model.The design process is to choose a suitable radius of the ring for a single probe antenna.Then, the suitable probe length and ring length are determined for the twoprobe antenna.Finally, isolation between the two probes is enhanced by insertion of an inductor coil between the probes.The operational characteristics of the prototype antenna at the frequency of 5.2 GHz are measured and compared with calculation results.It is evident that these results are in good agreement.The antenna achieved isolation in excess of 20 dB and VSWR less than 2 : 1 over the desired bandwidth and a bidirectional radiation pattern with 4 dBi gain.This antenna is suitable for Multiple-Input Multiple-Output (MIMO) system covering a long and narrow environment.
Keywords: Antenna Design and Analysis